M-currents (Kv7.2-7.3/KCNQ2-KCNQ3) Are Responsible for Dysfunctional Autonomic Control in Hypertensive Rats - Berg, Torill (Frontiers in Physiology, 2016)
Autonomic dysfunctions play important roles in hypertension, heart failure and arrhythmia, often with a detrimental and fatal effect. The present study analysed if these dysfunctions involved M-channels (members of the Kv7/KNCQ family) spontaneously hypertensive rats (SHR). Cardiac output and heart rate (HR) were recorded by a flow probe on the ascending aorta in anesthetized SHR and normotensive rats (WKY), and blood pressure (BP) by a femoral artery catheter. Total peripheral vascular resistance (TPR) was calculated. XE-991 (Kv7.1-7.4-inhibitor) reduced resting HR in WKY but only after reserpine in SHR. XE-991 increased TPR and BP baseline in both strains. Retigabine (Kv7.2-7.5-opener) reduced HR, TPR and BP, also after reserpine. Depolarization induced by 3,4-diaminopyridine (3,4-DAP), a voltage-sensitive K+ channel (Kv) inhibitor, activated release of both acetylcholine and norepinephrine, thus activating an initial, cholinergic bradycardia in SHR, followed by sustained, norepinephrine-dependant tachycardia in both strains. XE-991 augmented the initial 3,4-DAP-induced bradycardia and eliminated the late tachycardia in SHR, but not in WKY. The increased bradycardia was eliminated by hexamethonium and methoctramine (M2muscarinic receptor antagonist) but not reserpine. Retigabine eliminated the increased bradycardia observed in reserpinized SHR. XE-991 also increased 3,4-DAP-stimulated catecholamine release, but not after hexamethonium or reserpine. Conclusions: M-currents hampered parasympathetic ganglion excitation and, through that, vagal control of HR, in SHR but not WKY. M-currents also opposed catecholamine release in SHR but not in WKY. M-currents represented a vasodilatory component in resting TPR-control, with no strain-related difference detected. Excessive M-currents may represent the underlying cause of autonomic dysfunctions in hypertension.